Protein Inhibitor of NOS1 Plays a Central Role in the Regulation of NOS1 Activity in Human Dilated Hearts - Roselló-Lletí, Esther (Sci Rep, 2016)
An essential factor for the production of nitric oxide by nitric oxide synthase 1 (NOS1), major modulator of cardiac function, is the cofactor tetrahydrobiopterin (BH4). BH4 is regulated by GTP cyclohydrolase 1, the rate-limiting enzyme in BH4 biosynthesis which catalyses the formation of dihydroneopterin 3′triphosfate from GTP, producing BH4 after two further steps catalyzed by 6-pyruvoyltetrahydropterin synthase and sepiapterin reductase. However, there are other essential factors involved in the regulation of NOS1 activity, such as protein inhibitor of NOS1 (PIN), calmodulin, heat shock protein 90, and NOS interacting protein. All these molecules have never been analysed in human non-ischemic dilated hearts (DCM). In this study we demonstrated that the upregulation of cardiac NOS1 is not accompanied by increased NOS1 activity in DCM, partly due to the elevated PIN levels and not because of alterations in biopterin biosynthesis. Notably, the PIN concentration was significantly associated with impaired ventricular function, highlighting the importance of this NOS1 activity inhibitor in Ca(2+) homeostasis. These results take a central role in the current list of targets for future studies focused on the complex cardiac dysfunction processes through more efficient harnessing of NOS1 signalling.